Pengaruh Trend Fashion, Content Creator, dan Live Streaming terhadap Keputusan Pembelian Produk Fashion pada Pengguna Aplikasi Tiktok (Followers Tiktok @secaca.id) - Hasanah, Uswatun; Ajizah, Nur; Huda, Miftahul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to determine the effect of fashion trends, content creators, and live streaming on purchasing decisions for fashion products for TikTok application users both partially and simultaneously. The type of research used is explanatory using a quantitative approach. The data collection technique used a questionnaire. The sample used in this study was 116 respondents with purposive sampling method for sampling. The data analysis technique uses multiple linear regression analysis techniques through the SPSS 29 program. The results of this study indicate that fashion trends and content creators partially have a positive and significant effect on purchasing decisions, while live streaming partially has a positive but insignificant effect on purchasing decisions. And simultaneously fashion trends, content creators, and live streaming have a positive and significant effect on purchasing decisions by 68.5% and the remaining 31.5% is influenced by other variables not examined.